Transpubic Urethroplasty for Recurrent Urethral Strictures in Pelvic Fracture Urethral Distraction Defects: A Tertiary Care Centre Experience - M, Shivlingaiah (Asian Journal of Medical Research, 2018)
Background: Posterior pelvic fracture urethral distraction defect (PFUDD) is a challenging urologic problem that may result in complications, such as urinary incontinence and inability to void due to recurrent stricture leading to a lifelong disabling condition.The principal indication of transpubic urethroplasty is lengthy (3cms) recurrent (failed) repairs of posterior urethral stricture. Subjects and Methods: We reviewed case records of patients who presented with recurrent urethral stricture secondary to pelvic fracture urethral distraction defects from 2005 to 2010. Results: All 8 such cases were followed up for a period of 1-3 years. Overall stricture free rate was 75%. Conclusion: Transpubic urethroplasty appears to be an optimal substitute for recurrent stricture due to pelvic fracture urethral distraction defects (PFUDDs).